Methodologies of control strategies for improving energy efficiency in agricultural greenhouses. (20th November 2020) - Zhang, Shanhong; Guo, Yu; Zhao, Huajian; Wang, Yang; Chow, David; Fang, Yuan
Abstract: The greenhouse sector accounts for the largest portion of total final energy consumption in agriculture in most countries. One efficient way to minimize the total energy consumption in greenhouses is through the acceptable and efficient control strategy. The control strategy plays a very important role in maintaining comfortable inside climate and reducing energy consumption for the greenhouse, which could effectively adjust the equipment such as the heating/cooling, ventilation, shading system, and coordinate them with low energy operation. The objective of this article is to systematically review the methodologies of control strategies for improving energy efficiency in agricultural greenhouses, particularly for the low energy greenhouses. The methods section, including review methodology and brief methodology description for control strategies in greenhouses, have been first presented. Subsequently, results section introduces the significance of control strategy and types of control strategies in greenhouses; detailed methodologies of greenhouse control strategies including mathematical modelling study; physical experimental study; numerical simulations and parametric sensitivity analysis have been then systematically reviewed. Furthermore, more than 30 parameters affecting greenhouse performance have been analyzed and evaluated. This review could provide a guidance to probe into the advanced control strategies to reduce the energy consumption for the greenhouse and maintain suitable growing environment simultaneously. This work has also demonstrated several control perspectives on the future low energy greenhouse trends. Graphical abstract: Relationship among controller, greenhouse equipment supplied by thermal and electrical energy, controlled environmental factors (temperature, humidity etc.) and sensors in the greenhouse (a), detailed thermal environment inside the greenhouse (b). Image 1 Highlights: First review on greenhouse control strategy methodologies considering energy efficiency. Review on various greenhouses control technologies investigated via simulation/measurement. Parametric sensitivity analysis including diverse effects of 30+ parameters on greenhouse performance. Comparison and evaluation on control performance of different algorithms in greenhouses.